Primary Intracranial Parasagittal Angioleiomyoma: A Case Report of Uncommon Location of a Rare Tumor - Alturaiki, Jasmine; Alsalman, Hashem; Aljughiman, Abdullah; Ahmed, Fatima H.; Miliaras, Georgios (International Journal of Innovative Research in Medical Science, 2022)
Background: Angioleiomyoma is a soft tissue benign tumor that occurs mainly in subcutaneous tissue, involving the lower extremities in particular. We present a rare case of angioleiomyoma invading the central nervous system. Case description: A 17-year-old Saudi male presented with two months history of headache and vomiting. MRI revealed an intra-axial mass in the right parietal area. Macroscopically, the mass measuring 4.5×4×3 cm after was resected. Both imaging and histopathological findings were consistent with angioleiomyoma. In a period of 6 months of follow-up there was no recurrence of the tumor. Conclusion: Primary intracranial angioleiomyoma is an extremely uncommon tumor, though possible to happen.